CONSOLIDATED REPORTS. - Bordner, H. W. (The Accounting Review, 1938)
Abstract It would seem appropriate that Some Tentative Propositions Underlying Consolidated Reports presented at the last annual meeting of the American Accounting Association, be expanded to include the more complete discussion of the reasoning followed in arriving at the conclusions it contains. The treatment in consolidation of earned surplus of subsidiaries arising prior to date of acquisition of control. The accrual of equities in undistributed earnings of subsidiaries in accounts of the parent. The determination of reserves for losses on investments in subsidiaries based on ultimate realization rather than on amounts of operating losses. The exclusion from consolidation of nonhomogeneous subsidiaries. It is submitted that these propositions are neither in accordance with generally accepted practice nor based on any logical assumptions. In effect they state that the parent's equity in earnings of a subsidiary during the period when an interest was owned less than controlling may constitute earned surplus to the parent only if received prior to acquisition of control but not if received after acquisition of control.